(untitled) (Socio-economic relations in the digital society, 2019)
In this paper quantitative indicators of capitalization rate (CR) for Ukraine and for some foreign countries were compared, the dynamics of change was analyzed and common trends of changes were identifi ed. It is shown that in the conditions of the economic crisis the reliable criterion for determining the state of the market is CR calculated by the method of extraction. Accordingly, the reliability of determining CR by the cumulative method is reduced. The research of the market’s characteristics changes that are observed in the development of the economic crisis, is made in relation to the residential and commercial real estate price indices which are determined by the means of an independent expert review. To increase the accuracy and reliability of the evaluation work results by minimizing additional errors caused by growing uncertainty of numerical value of CR it is off ered to calculate CR focusing primarily on market method of extraction. The aim of the article is to analyze the diff erences in the dynamics of changes of CR in Ukraine and abroad; to identify economic reasons of these diff erences and to study the possibilities to increase the reliability of CR determination. The conducted analysis showed common for Ukraine and foreign countries trend to subsequent decrease of actual CR, calculated by the method of extraction for the market of commercial and residential real estate.Comparison of levels and dynamics of the CR demonstrates that Ukraine is not unique.On the contrary, the analysis given above shows that, despite the existence of the crisis, the economy of the country is similar to countries with developed market economies, and it has the same global trends.